2021
DOI: 10.1002/cnma.202100104
|View full text |Cite
|
Sign up to set email alerts
|

Promotional Effect of Ni−Sn Interaction over Ni Supported on Sn‐incorporated MCM‐41 Catalysts for CO2 Reforming of CH4

Abstract: Sintering of active Ni sites and deposition of coke remain challenging issues for catalytic dry reforming of methane. Herein, Ni supported on the Sn‐incorporated MCM‐41 catalysts were synthesized and tested for DRM process. The structural and physicochemical properties of fresh and spent samples were studied by N2 adsorption‐desorption, XRD, H2‐TPR, XPS, TEM, STEM‐EDS, Raman, and TGA techniques. It was revealed that Sn addition improved the dispersion and decreased the size of active Ni nanoparticles by tuning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…However, the presence of CaO caused a shift to a higher temperature, because of the strong CaO–support interaction making it more challenging to reduce the sample. 48,49…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of CaO caused a shift to a higher temperature, because of the strong CaO–support interaction making it more challenging to reduce the sample. 48,49…”
Section: Resultsmentioning
confidence: 99%
“…However, the presence of CaO caused a shift to a higher temperature, because of the strong CaO-support interaction making it more challenging to reduce the sample. 48,49 It was well found that the catalytic efficiency and activity of supported catalysts were improved by the nature of the support. 50 In particular, the basic sites effectively improved catalytic performance.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…[5] After removal of the template the MCM material class offers highly ordered mesopores, which allow e. g. the formation of nanoreactors in the pores. [6][7][8] Further due to mesoporosity (pore sizes between 2 to 50 nm), MCM materials provide very high surface area (up to 1500 m 2 g À 1 ), which is very promising for different fields of application like catalysis, [9][10][11][12][13][14] medicine, [15][16][17][18][19][20] proton conduction [21][22][23][24][25][26][27] or purification/adsorption processes [28][29][30][31][32] and immobilization processes, [33][34][35][36] like e. g. immobilization of catalysts. [37][38][39][40] Another very attractive characteristic of MCM materials is the fact that these materials consist only of silica (SiO 2 ), which is non-toxic for our body, so the application in and on our body is possible.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, small amount of chemical or structural promoters can alter catalytic performances significantly, and various promoters having positive contributions of activity and stability such as noble metals, transition metals, alkali and alkali-earth metals and rare earth metals are generally incorporated on the cobalt-based FTS catalysts [23][24][25]. Among those promoters, Tin (Sn) has not been well-reported as a chemical promoter on the FTS catalysts as far as we know, even though Sn promoter has been largely applied for various reforming reactions [26,27], dehydrogenation of alkanes [28], CO 2 hydrogenation [29], dimethyl ether (DME) synthesis from syngas [30,31] and so on. The crucial roles of Sn promoter are to change the surface affinity as well as to modify the electronic states of active metals.…”
Section: Introductionmentioning
confidence: 99%